2019
DOI: 10.5194/bg-16-289-2019
|View full text |Cite
|
Sign up to set email alerts
|

The post-monsoon carbon biogeochemistry of the Hooghly–Sundarbans estuarine system under different levels of anthropogenic impacts

Abstract: Abstract. The present study focused on understanding differences in the post-monsoon carbon (C) biogeochemistry of two adjacent estuaries undergoing different levels of anthropogenic stresses by investigating anthropogenically influenced Hooghly estuary and mangrove-dominated estuaries of the Sundarbans in the north-eastern India. The salinity of well-oxygenated estuaries of the Sundarbans (DO: 91 %–104 %) varied over a narrow range (12.74–16.69) relative to the Hooghly estuary (0.04–10.37). A mixing model sug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 90 publications
6
32
0
Order By: Relevance
“…The waters around mangroves are known to have a buffering capacity against coastal acidification (Sippo et al, 2016;Maher et al, 2018). In the present study, the data for the water around mangroves (and the pore water or groundwater data from other studies) consistently show a Talk:DIC ratio >1, [Dutta et al, 2019]), groundwater-and pore water-derived DIC (δ 13 CDIC = -18.0‰ in Sundarban [Dutta et al, 2019]; -14.5‰ to -10.0‰ [Maher et al, 2013]), and degradation and/or decomposition of marine phytoplankton (δ 13 CPOC = -21.8‰ [MEM, present study]; -22.0‰ to -20.0‰ [Rosentreter et al, 2018]). However, we found no significant correlation between δ 13 CDIC and δ 13 CPOC, which might be because the sources were well-mixed.…”
Section: Mechanisms For Influx or Reduced Efflux Of Co2supporting
confidence: 72%
See 2 more Smart Citations
“…The waters around mangroves are known to have a buffering capacity against coastal acidification (Sippo et al, 2016;Maher et al, 2018). In the present study, the data for the water around mangroves (and the pore water or groundwater data from other studies) consistently show a Talk:DIC ratio >1, [Dutta et al, 2019]), groundwater-and pore water-derived DIC (δ 13 CDIC = -18.0‰ in Sundarban [Dutta et al, 2019]; -14.5‰ to -10.0‰ [Maher et al, 2013]), and degradation and/or decomposition of marine phytoplankton (δ 13 CPOC = -21.8‰ [MEM, present study]; -22.0‰ to -20.0‰ [Rosentreter et al, 2018]). However, we found no significant correlation between δ 13 CDIC and δ 13 CPOC, which might be because the sources were well-mixed.…”
Section: Mechanisms For Influx or Reduced Efflux Of Co2supporting
confidence: 72%
“…The Hooghly River is the main "artery" (Ray et al, 2018a) and only possible source of riverine freshwater for the Indian Sundarbans, and the adjacent sea is the BoB. For this reason, the near-zero salinity regime of the Hooghly River and the northern BoB have been universally used in previous works (Ray et al, 2015(Ray et al, , 2018aRay and Shahraki, 2016;Dutta et al, 2019) as freshwater and marine end-members, respectively, in their mixing models for the Indian part of the Sundarbans. As in these previous studies, we defined the observed salinity at the Diamond Harbour station (salinity approx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10.1029/2020JG006144 14 of 22 ( Akhand et al, 2016;Dutta, Kumar, Mukherjee, Sanyal, & Mukhopadhyay, 2019). The observed pCO (water) and air-water CO 2 efflux from the Dhamra were similar to those of the nearby Mahanadi Estuary (Dey et al, 2013;Ganguly et al, 2011).…”
Section: Effect Of Reduced Riverine Freshwater On Inorganic Carbon Dynamicsmentioning
confidence: 55%
“…Authors' Response: Considering Reviewer 2's comments and rechecking previous studies (for example Ray et al 2018;Dutta et al 2019) in Sundarban (Indian part) on CO2/ carbon dynamics, we decided to eliminate all the wordings and sentences, which seems there is no riverine connection (or almost none), and replace the confusing phrases like "negligible riverine freshwater input" to "indirect and lesser riverine freshwater input". This is because the quantification of riverine freshwater input from Hooghly River to the Sundarban (Indian part) was not done previously using hydrological modelling and out of scope for the present study, It is well established fact, that Indian part of Sundarbans are not getting riverine freshwater directly from its upstream rivers (for example Matla, saptamukhi, Thakuran etc.…”
mentioning
confidence: 99%